Gaze cuing of attention in snake phobic women: the influence of facial expression - Pletti, Carolina; Dalmaso, Mario; Sarlo, Michela; Galfano, Giovanni (Frontiers in Psychology, 2015)
Only a few studies investigated whether animal phobics exhibit attentional biases in contexts where no phobic stimuli are present. Among these, recent studies provided evidence for a bias toward facial expressions of fear and disgust in animal phobics. Such findings may be due to the fact that these expressions could signal the presence of a phobic object in the surroundings. To test this hypothesis and further investigate attentional biases for emotional faces in animal phobics, we conducted an experiment using a gaze-cuing paradigm in which participants’ attention was driven by the task-irrelevant gaze of a centrally presented face. We employed dynamic negative facial expressions of disgust, fear and anger and found an enhanced gaze-cuing effect in snake phobics as compared to controls, irrespective of facial expression. These results provide evidence of a general hypervigilance in animal phobics in the absence of phobic stimuli, and indicate that research on specific phobias should not be limited to symptom provocation paradigms.